(untitled) (Research, Society and Development, 2020)
The concept of childhood is widespread in several areas of knowledge and common sense. It is through a social construction, over the centuries, that you can understand the place that knowledge about childhood and children occupies today. Based on this, the role that will occupy the course of its entire history is related to the implementation of public policies aimed at childhood and the current reality. This is a bibliographic review of the literature, with a qualitative and descriptive approach in order to relate how nurses’ actions in the face of child violence and describe relevant considerations in the face of child violence. From this preliminary reading, 17 articles were selected that maintain consistency with the descriptors presented above and with the objectives of the study. After reflective reading, three categories emerged: Requirements for child health care in the face of violence; Repercussions of child violence on the child’s growth and development; Nursing Contributions in the assistance to the child victim of Violence. Once started in the analysis categories, it moves on to the final stage of inference and discussion of the data used, using the backing or using the articulation between the content recorded in the scientific productions and a critical-reflexive attitude of the researchers. It is concluded that it is necessary the professional skill of a nurse in the identification of cases of abuse, whether sexual, domestic violence, among others, the same way that it is fundamental to be alert and recognize suspicious foreshadows and conduct.